Kenya - Kiaragana Village - Njeru-Ri - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Talking to Kenyan farmer Emily Marigu on adaptation and mitigation to climate change. Emily has adapted to the changing climate through crop diversification by including sweet potatoes. These have now become even more important for her than her staple crops beans and maize.